In situ detection of estrogen receptor dimers in breast carcinoma cells in archival materials using proximity ligation assay (PLA). Issue 165 (January 2017) - Iwabuchi, Erina; Miki, Yasuhiro; Ono, Katsuhiko; Onodera, Yoshiaki; Suzuki, Takashi; Hirakawa, Hisashi; Ishida, Takanori; Ohuchi, Noriaki; Sasano, Hironobu
Highlights: We did firstly succeed in the visualization of ER dimeric proteins using PLA. Estradiol administration induced ERα homodimers in breast carcinoma cell lines. ER dimeric protein was also visualized in clinical specimens of breast cancer. Abstract: Estrogen receptor (ER) is required for carcinoma cell proliferation in the great majority of breast cancer and also functions as a dimer. ER dimeric proteins have been largely identified by BRET/FRET analyses but their in situ visualization have not yet been reported. Recently, in situ Proximity Ligation Assay (PLA) has been developed as the methods detecting protein interactions in situ . Therefore, in this study we firstly demonstrated the dimerization of ERα in breast carcinoma cell lines and tissues using PLA. The human breast carcinoma cell lines MCF-7, T-47D and MDA-MB-231 were used in this study. Cells were treated with ER agonist or antagonist and fixed in 4% PFA, and ER dimers were subsequently detected using PLA. The evaluation of ER dimers in breast carcinoma cell lines were quantified by measuring the area of dots localized in the nuclei using image analysis. We also firstly demonstrated the visualization of ER dimer patterns in 10% formalin-fixed paraffin-embedded tissues of breast cancer using PLA technique. Estradiol (E2) administration induced ERα homodimers in the nuclei of MCF-7 and T-47D but not in ER-negative MDA-MB-231. 4-OH tamoxifen also induced ERα homodimers but the subcellular localization of these ERα homodimers was predominant in cytoplasm instead of the nuclei induced by E2 treatment. ICI182, 780 treatment did decrease the number of formation of ERα homodimers in MCF-7. In breast cancer patients, ERα PLA score was significantly correlated positively with ERα- or PgR (progesterone receptor) immunohistochemical scores and inversely with Ki-67-labeling index, respectively. We also demonstrated the ERα/β heterodimer as well as ERα homodimers in both breast carcinoma cell lines and surgical pathology specimens. In summary, we did firstly succeed in the visualization of ER dimeric proteins using PLA method. The evaluation of ER dimer patterns could provide pivotal information as to the prediction of response to endocrine therapy of breast cancer patients.